Analisis Harga, Kualitas Produk dan Kepuasan Terhadap Loyalitas Pelanggan Mcdonald Gresik: Studi pada Pengguna Aplikasi Limited Time Offer - Rosalina, Patrisya; Surianto, Moh Agung (As-Syirkah: Islamic Economic & Financial Journal, 2024)
This study aims to examine Price, Product Quality, Satisfaction with Mcdonalds Gresik Customer Loyalty in the use of the Limited Time Offer application. The population in this study is all people who use or customers who use the Limited Time Offer application in Gresik using the nonprobability sampling method of 76 respondents as a sample. The source of data in this study is primary data, which is the result of distributing questionnaires to respondents. The type of data used is subjective data in the form of written responses as questionnaire responses. The analysis model used in this study is a multiple linear regression analysis model. To determine the significance of research variables partially on work productivity, t-test techniques are used. By using a level of 5% or 0.05. The results show that Price affects Loyalty but Product Quality and Satisfaction do not affect McDonalds Gresik Customer Loyalty.